2022
DOI: 10.3389/fphar.2022.991917
|View full text |Cite
|
Sign up to set email alerts
|

Scutellaria baicalensis Georgi regulates REV-ERBα/BMAL1 to protect against skin aging in mice

Abstract: Scutellaria baicalensis Georgi (SBG) is a traditional Chinese medicine widely used to treat disorders such as hypertension, dysentery and hemorrhaging. Here, we aimed to assess the pharmacological effects of SBG on skin aging and to investigate the underlying mechanisms. Mice with skin aging were established by treatment with D-galactose and ultraviolet-B. SBG (topical application) showed a protective effect on skin aging in mice, as evidenced by less formation of skin wrinkles, higher levels of SOD (superoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Joo JH et al showed that BMAL1 expression was significantly downregulated in UV radiation-treated human keratinocytes and that BMAL1 ameliorated UV radiation-induced DNA damage in human keratinocytes [ 19 ]. Sun G et al suggested that upregulation of BMAL1 could ameliorate UV-induced skin aging in mice by suppressing oxidative stress levels [ 20 ]. Sun Y et al revealed that BMAL1 and CLOCK have important functions in regulating apoptosis and DNA damage response in human keratinocytes induced by UVB radiation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Joo JH et al showed that BMAL1 expression was significantly downregulated in UV radiation-treated human keratinocytes and that BMAL1 ameliorated UV radiation-induced DNA damage in human keratinocytes [ 19 ]. Sun G et al suggested that upregulation of BMAL1 could ameliorate UV-induced skin aging in mice by suppressing oxidative stress levels [ 20 ]. Sun Y et al revealed that BMAL1 and CLOCK have important functions in regulating apoptosis and DNA damage response in human keratinocytes induced by UVB radiation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It re-seeds in China and Northeast Asia, including Siberia and north of the Yangtze River [ 15 ]. The pharmacological effects of SBG protection from UV damage in aging skin provide anti-allergic [ 16 ] and anti-inflammatory effects in AD [ 17 ]. Moreover, Raphanus sativus Linne is a Chinese medicine made from the seeds of cruciferous or congenital plants that have been re-seeded in the Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%